Pengaruh Job Crafting terhadap Employee Well-being - Widi Setiati Nugraha; Dewi Sartika; Rizka Hadian Permana (Bandung Conference Series: Psychology Science, 2023)
Abstract. In this digital era, the process of marketing a product is very fast and all-technology so that digital marketing is a division that is needed today, allowing employees to do job crafting. The number of employees working from digital marketing does not make employee welfare low. The purpose of this study was to determine whether there is an influence between job crafting and employee welfare. This research is a quantitative study with a population and sample, namely employees of the digital marketing division of PT Sebelas April Lian Mipro who opened 32 people. This study uses the job crafting scale and employee well being scale which have been adapted and tested for validity and reliability. The result of this study is that job crafting has a significant effect on employee welfare by 46.7%. The form that has the highest impact is an increase in challenging job demands followed by a decrease in hindering job demands, and an increase in structural work resources. (max. 250 words). Keywords: Job Crafting, Employee Well-Being, Digital Marketing. Abstrak. Di era digital seperti saat ini, proses pemasaran sebuah produk menjadi sangat cepat dan serba teknologi sehingga pemasaran digital menjadi divisi yang dibutuhkan saat ini sehingga memungkinkan karyawan melakukan job crafting. Banyaknya karyawan pekerjaan dari pemasaran digital tidak membuat rendahnya kesejahteraan karyawan. Tujuan penelitian ini adalah untuk mengetahui apakah terdapat pengaruh antara job crafting dengan kesejahteraan karyawan. Penelitian ini merupakan penelitian kuantitatif dengan populasi dan sampel yaitu karyawan divisi digital marketing PT Sebelas April Lian Mipro yang membuka 32 orang. Penelitian ini menggunakan alat ukur job crafting scale dan employee well being scale yang telah diadaptasi dan diuji validitas dan reliabilitasnya. Hasil dari penelitian ini adalah bahwa job crafting memiliki pengaruh yang signifikan terhadap kesejahteraan karyawan sebesar 46,7%. Dengan bentuk yang memiliki pengaruh paling tinggi adalah peningkatan tuntutan pekerjaan yang menantang dilanjut dengan penurunan tuntutan pekerjaan yang menghambat, dan peningkatan sumber daya pekerjaan struktural. (maks. 250 kata). Kata Kunci: Job Crafting, Employee Well-Being, Digital Marketing.